Is God Everywhere? An Anthropological Theology of God and the Cosmos - Richard Tambwe (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2025)
This article addresses the “where” question for understanding who God is for Christians. It explores the divine presence through the lenses of theological cosmology, Christology, and pneumatology. Limiting the investigation to (and even connecting) creation and redemption, and engaging contemporary theologians such as Adolphe Gesché, Alejandro García-Rivera, Ian McFarland, Kathryn Tanner, and Veli-Matti Kärkkäinen, it discusses God’s immanence and transcendence, culminating in spiritual panentheism. Ultimately, places where God is encountered are sacred with two characteristics of God’s glory descending as “rain,’ while worship ascends as “vapor” (upward and forward). As human, we are in this world first, a world to cultivate as cosmos (i.e., beautiful and shared world), although our destiny is elsewhere: where our world corresponds to God’s fullness. This means being at home in the cosmos, being at home in the flesh, and seeing God in all things. God is everywhere; we just need to experience divine presence by seeing all things in God. This implies lived faith in everyday life: now in the present, here and there, everywhere.